Analisis Perencanaan dan Penggunaan Keuangan Mahasiswa pada Masa Covid - Rakhma Wati Purba; Sri Winda Hardiyanti Damanik (Universitas Batanghari Jambi, 2021)
This study aims to analyze the financial planning of students and analyze the use of student finances in the continuity of paying tuition fees. The type of research is descriptive quantitative research. This research was conducted on S1 Management students of STIE Bina Karya Tebing Tinggi with population of 2900 with a sample of 352 students, with variable X = financial behavior pattern and variable Y = financial stress. Questionnaire using Googleform Data processing using SPSS Windos program. The results showed that the ability of students to make financial planning in the face of the Covid 19 Pandemic was good, which could be seen from the average value of the financial behavior pattern variable which was 2.42 with high category, although there were some behaviors that had to be improved in order to minimize or reduce the financial stress of the student concerned. For the financial stress variable, it can be seen that students have a moderate level of financial stress, with an average value of 2.09. However, it is necessary to make and record budget and expenditure plans, both daily and monthly for the pocket money they receive so that all forms of income and expenses from students can be seen and also controlled by the students themselves.